Cancer of Pharyngoesophageal Junction: A Different Subtype From Hypopharyngeal and Cervical Esophageal Cancer? - Li, Xiaoyu; Ai, Dashan; Chen, Yun; Liu, Qi; Deng, Jiaying; Zhu, Hongcheng; Wang, Ying; Wan, Yue; Xie, Yue; Chen, Yanan; Chen, Weiwei; Fan, Jianhong; et al. (Frontiers in Oncology, 2021)
Background Squamous cell cancers in the hypopharynx (HP) and cervical esophagus (CE) are different diseases with different staging systems and treatment approaches. Pharyngoesophageal junction (PEJ) tumor involves both the hypopharynx and the cervical esophagus simultaneously, but few reports focused on PEJ tumors. This study aimed to clarify clinical characteristics and the treatment approaches of PEJ tumors. Patients and Methods A total of 222 patients with squamous cell carcinoma in the HP, PEJ, and CE were collected between January 2008 and June 2018 in Fudan University Shanghai Cancer Center. We compared different lymph node metastatic patterns of three diseases above and the survival of different tumor locations, different lymph node metastasis, and different radiotherapy approaches. Results For HP, PEJ, and CE cancer, the upper and middle cervical lymph node metastatic rates were 85.7%, 47.1%, and 5.8%, respectively; the lower cervical lymph node metastatic rates were 36.7%, 42.9%, and 35.0%, respectively; and the mediastinal lymph node metastatic rates were 2.0%, 72.9%, and 80.6%, respectively. The 3-year overall survival rates were 69.5% in the HP group, 52.0% in the PEJ group, and 69.6% in the CE group (p = 0.024). No survival differences were found between the involved-field-irradiation and elective-node-irradiation subgroups among PEJ tumors (p = 0.717 for OS and p = 0.454 for PFS, respectively). Conclusion HP cancers had a high prevalence in all cervical lymph node metastases, while CE cancers had a lower prevalence in the cervical and mediastinal lymph node metastases. PEJ cancer had the combined metastatic patterns of both HP and CE cancers. Involved field irradiation was feasible in chemoradiotherapy for PEJ cancers.